Pengaruh penambahan Magnesium pada remelting piston motor bekas menggunakan tungku induksi terhadap kekuatan fatik dan porositas - Mahmud Yunus; Tri Cahyo Wahyudi; Eko Nugroho (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2022)
Metal is a natural material that is very useful in various aspects of human life, one of which is non-ferrous metal material, the metal does not contain iron elements such as copper, aluminum, tin. The purpose of this study was to determine the effect of the addition of Magnesium on fatigue and porosity testing, using the casting method of used Aluminum piston motor using an induction furnace with a pouring temperature of 700°C. In the fatigue test, the addition of Magnesium element by 1% gets a cycle value of 5,100, and a variation of 1.5% gets a cycle value of 5,220 and a 2% variation gets a cycle value of 5,420. As for the porosity test, the addition of Magnesium element by 1% gets a porosity value of 9.2% and a variation of 1.5% gets a porosity value of 4.5% and a variation of 2% gets a porosity value of 3.5%.